Recruiting and Retaining Members in Agricultural Organizations - Ricky W. Telg (EDIS, 2018)
Many organizations struggle with recruiting new members and retaining current members. The UF/IFAS PIE Center conducted membership surveys of the Florida Cattlemen’s Association and Florida CattleWomen to aid both groups in their membership efforts. This 3-page document discusses common membership barriers and practices in order to help agricultural organizations be better equipped to attract new members and keep current ones. Written by Ricky Telg and published by the UF/IFAS Department of Agricultural Education and Communication, March 2018. http://edis.ifas.ufl.edu/wc300